2018
DOI: 10.1161/circimaging.117.007512
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Phasic Function by Cardiac Magnetic Resonance Feature Tracking Is a Strong Predictor of Incident Cardiovascular Events

Abstract: Background: The prognostic importance of left atrial (LA) dysfunction is increasingly recognized. Magnetic Resonance Imaging (MRI) can provide excellent visualization of the left atrial wall. We aimed to study the association of LA dysfunction measured using feature-tracking MRI with incident adverse cardiovascular events among subjects with or without HF at baseline. Methods and Results: We prospectively studied 640 adults without HF (n=419), HF with preserved ejection fraction (HFpEF, n=101), or HF with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 32 publications
7
69
1
3
Order By: Relevance
“…The authors who reported these findings did not provide explanations for their results . The reduced LA reservoir function is strong predictor of incident cardiovascular events, atrial fibrillation occurrence and recurrence, and worse outcome in patients with heart failure with preserved ejection fraction . Our present findings showed that athletes had reduced LA pump function.…”
Section: Discussioncontrasting
confidence: 64%
“…The authors who reported these findings did not provide explanations for their results . The reduced LA reservoir function is strong predictor of incident cardiovascular events, atrial fibrillation occurrence and recurrence, and worse outcome in patients with heart failure with preserved ejection fraction . Our present findings showed that athletes had reduced LA pump function.…”
Section: Discussioncontrasting
confidence: 64%
“…Clinical importance of the left atrial functional analysis has been emphasized in many echocardiography studies particularly the prognostic value of left atrial measurements for patients with heart failure with preserved ejection fraction (Morris et al, 2011;Santos et al, 2014Santos et al, , 2016Cameli et al, 2017;Liu et al, 2018). Clinical studies that used MRI sequences for cardiac functional measurements also led to similar findings and demonstrated the prognostic values of the left atrial functional parameters in heart failure patients (Von Roeder et al, 2017;Chirinos et al, 2018). One of the significant advantages of the proposed method is that it is fully automated and, therefore, will allow for analyzing a large number of MRI images which otherwise tedious and time-consuming.…”
Section: Discussionmentioning
confidence: 84%
“…Importance of LA phasic function evaluation is increasingly recognized for its incremental value in terms of prognosis and risk stratification in various disease states [1, 2328]. We studied the clinical relevance and prognostic utility of disturbed LA phasic function in heterogeneous population associated with hypertension or AF.…”
Section: Discussionmentioning
confidence: 99%
“…LA enlargement in the patients with hypertension or AF is a common clinical phenomenon. However, the prognostic importance of LA phasic functions has more recently been recognized [1]. The LA modulates left ventricular (LV) filling through three components: reservoir, conduit and booster pump phase.…”
Section: Introductionmentioning
confidence: 99%